Translation and Validation of the Muslim Experiential Religiousness Scale for Pakistani Muslim Adults - Abbasi, Sitara (Journal of religion and health, 2026)
In this cross-sectional study, the subjects were 570 adults within the age range of 18-60 years (M = 24.77 SD = 6.86). The study aimed to translate Muslim Experiential Religiousness Scale (MERS) into Urdu language and established its construct validity in Pakistani culture. Construct validity of MERS was established through Confirmatorty Factor Analysis, and psychometric properties of MERS were determined. Construct validity and reliability were ascertained, and the goodness of fit was determined. Findings revealed significant differences across gender. Future implications were also discussed.